2019
DOI: 10.12688/f1000research.16040.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the geriatric curriculum implemented at Shiraz University of Medical Sciences, Iran, since 2017: A qualitative study

Abstract: Recently, there has been an increase in life expectancy due Background: to improvements in nutrition, health, and sanitation. The aim of this study was to evaluate the geriatric curriculum in the field of general medicine at Shiraz University of Medical Sciences (SUMS), Iran to improve the quality of services provided to this population in the community.This was a qualitative study. Six educational hospitals and Methods: ambulatory centers of Shiraz University of Medical Sciences participated in this study. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These results, consistent with other results of other studies (7,10,12,13,18,19,21,22,33,34), showed that it is possible to promote men`s participation in sexual and reproductive health using an integrated designed program, focusing on reforming the educational systems, adopting appropriate health system policies, government support, and socio-cultural policies (44). Therefore, it is expected that the model presented in this study can enhance men`s participation in sexual and reproductive health areas including the participation of men in providing safe cares for mothers, prevention of violence against women, counseling on the formation of high-risk sexual behaviors, education on gender equality, protecting the reproductive health of self and spouse, and so on (45).…”
Section: Discussionmentioning
confidence: 97%
“…These results, consistent with other results of other studies (7,10,12,13,18,19,21,22,33,34), showed that it is possible to promote men`s participation in sexual and reproductive health using an integrated designed program, focusing on reforming the educational systems, adopting appropriate health system policies, government support, and socio-cultural policies (44). Therefore, it is expected that the model presented in this study can enhance men`s participation in sexual and reproductive health areas including the participation of men in providing safe cares for mothers, prevention of violence against women, counseling on the formation of high-risk sexual behaviors, education on gender equality, protecting the reproductive health of self and spouse, and so on (45).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, some believe that the existence of trained nursing educators is one of the essential principles of ethics education. In this regard, Gorgulo believes that teaching ethics requires first, the knowledge and skills of teachers of ethics (112). in order to prepare nursing students for facing the ethical challenges of clinical practice, ethics educators are required to have pure experiences in the field of clinical practice and a sound theoretical knowledge base in the field of ethics (76).…”
Section: Discussionmentioning
confidence: 99%
“…In their cross sectional study, 60 out of 200 studied neonates died (30%), the median CRIB was higher in died patients. Consequently, the CRIB could be a reliable method to predict mortality and determine disease severity in neonates; they also recommended the utilization of CRIB even for patients who admitted to NICU (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%